Ekstrakharuan(Channa striata)secara efektif menurunkan jumlah limfosit fase inflamasi dalam penyembuhan luka (Extract of haruan (Channa striata) decreases lymphocyte count in inflammatory phase of wound healing process effectively) - Arisa Izzaty; Nurdiana Dewi; Dewi Indah Noviana Pratiwi (Journal of Dentomaxillofacial Science, 2014)
Haruan is river-water fish usually consumed by South Kalimantan people. Haruan extract contains albumin, Zn, Fe,Cu and unsaturated fatty acid which can act as antiinflammatory substances and accelarate wound healing. The aim ofthis study is to examine effectiveness of haruan extract on lymphocyte count in infammatory phase of wound healingprocess and compare it to ibuprofen. This study used true experimental method with post-test only control group designand simple random sampling. Samples were divided into 5 treatment groups:which were given the extract for 7 sevendays: 25% haruan extract group, 50% haruan extract group, 100% haruan extract group, negative control K(-) usingaquadest, positive control K(+) given ibuprofen suspension with dosage of 20mg/kg weight/day. Lymphocyte cells wereobserved using microscope and counted per field of view. Lymphocyte count reached its peak on day 5. Lymphocytecount means in each group were 4,2 ± 0,566; 1± 0,000; 3,8 ± 2,546; 7,1 ± 0,141; dan 7,5 ± 3,818 respectively. Two way ANOVA and post hoc LSD tests showed that lymphocyte count significantly decreased in 50% and 100% treatmentgroups (p<0,05) and has equal effect with ibuprofen in decreasing lymphocyte count. This study concluded that haruanextract significantly decreased lymphocyte count in wound healing process.